Pojęcie klasy średniej a kategoria małego i średniego przedsiębiorstwa prywatnego - Łuczka, Teresa (Wydział Prawa i Administracji UAM, 1995)
Traditionally, the concept of the middle class is defined by the determining of its place in the general structure of a society against the background of two other classes poles apart and are defined as the high and the low class. The in-between position of the middle class in the social structure determines its main characteristics: private ownership and work performed personally by the owner. Those two features differentiate the middle class from the other two classes. So positioned in that structure, the middle class has formed over the years of its development a separate type of business whose character is determined by certain structural quality characteristics. The process of classification and aggregation ofthat type of business is carried out on temporary basis through the defining of quantity features because quality features are neither measurable nor countable. This assumes a relation of adequacy between the character of the business (defined by its quality features) and its size (defined by its quantity features). This relation should be perceived in the process of the measurement of the size, the classification and aggregation of an enterprise ofthat type.
Concept of the middle class and a category of small and medium-size private businesses